Targeting c-Myc: JQ1 as a promising option for c-Myc-amplified esophageal squamous cell carcinoma. (10th April 2018) - Wang, Jingyuan; Liu, Zhentao; Wang, Ziqi; Wang, Shubin; Chen, Zuhua; Li, Zhongwu; Zhang, Mengqi; Zou, Jianling; Dong, Bin; Gao, Jing; Shen, Lin
Abstract: c-Myc amplification-induced cell cycle dysregulation is a common cause for esophageal squamous cell carcinoma (ESCC), but no approved targeted drug is available so far. The bromodomain inhibitor JQ1, which targets c-Myc, exerts anti-tumor activity in multiple cancers. However, the role of JQ1 in ESCC remains unknown. In this study, we reported that JQ1 had potent anti-proliferative effects on ESCC cells in both time- and dose-dependent manners by inducing cell cycle arrest at G1 phase, cell apoptosis, and the mesenchymal-epithelial transition. Follow-up studies revealed that both c-Myc/cyclin/Rb and PI3K/AKT signaling pathways were inactivated by JQ1, as indicated by the downregulation of c-Myc, cyclin A/E, and phosphorylated Rb, AKT and S6. Tumor suppression induced by JQ1 in c-Myc amplified or highly expressed xenografts was higher than that in xenografts with low expression, suggesting its potential role in prediction. In conclusion, targeting c-Myc by JQ1 could cause significant tumor suppression in ESCC both in vitro and in vivo . Also, c-Myc amplification or high expression might serve as a potential biomarker and provide a promising therapeutic option for ESCC. Highlights: No targeted drugs were available for ESCC, and we first found targeting c-Myc by JQ1 induced significant tumor suppression in ESCC both in vitro and in vivo PDX models. The mechanisms underlying the inhibitory effect of JQ1 were via inactivating of c-Myc/cyclin/Rb as well as PI3K/AKT pathways. We proposed that c-Myc amplification or high expression was the potential predictor for screening suitable ESCC patients receiving JQ1.